Traffic lights and health claims: a comparative analysis of the nutrient profile of packaged foods available for sale in New Zealand supermarkets. (4th June 2013) - Rosentreter, Simone C.; Eyles, Helen; Ni Mhurchu, Cliona
Abstract Objective: To assess the application of Multiple Traffic Light (MTL) nutrition labels and the Food Standards Australia New Zealand (FSANZ) Nutrient Profiling Standard Calculator (NPSC) to foods and their agreement in classification of foods. Methods: MTL and NPSC criteria were applied to selected packaged food products available in New Zealand (NZ) supermarkets in 2011: 157 breakfast cereals; 128 cereal bars; 40 pizzas; 69 sausages and hotdogs; and 13 burgers. A points‐based system combined MTL criteria into an overall score to enable comparison of food classification by the two systems. Results: Based on NPSC criteria, 156 (38%) NZ packaged food products were eligible to carry a health claim and thus classified as 'healthy'; 251 were 'less healthy'. Based on MTL criteria most 'healthy' products (61%) would also receive one red light. Using the MTL score, only 14% of products were classified as 'healthy'. Percentage agreement between the two systems was 73%. Conclusions: More than half of NZ packaged foods are 'less healthy' according to criteria underpinning two front‐of‐pack labelling systems. A number of foods eligible to carry health claims would display at least one red traffic light if MTL were introduced.